Teaching Communication Skills to Hospice Teams: Comparing the Effectiveness of a Communication Skills Laboratory With In-Person, Second Life, and Phone Role-Playing. (September 2014) - Hamilton, Gillian; Ortega, Rosio; Hochstetler, Vicki; Pierson, Kristen; Lin, Peiyi; Lowes, Susan
Introduction: Communication skills are critical in hospice care but challenging to teach. Therefore, a hospice agency developed a communication skills laboratory for nurses and social workers. Methods: Learners role-played 3 common hospice scenarios. The role-play modalities were in-person, Second Life, and telephone. Learners were scored on 4 communication aspects. Results: Learners in all modalities rated the laboratory as very effective. However, learners in the Second Life and phone modality showed greater improvements from scene 1 to 3 than those in the in-person modality. There were no significant differences in improvement between the Second Life and phone modalities. Conclusion: Results support the effectiveness of this communication skills laboratory while using different teaching modalities and show phone and Second Life role-plays were more effective than an in-person role-play.